Adrift in the Arctic ice pack : from the history of the first U.S. Grinnell expedition in search of Sir John Franklin - Kane, Elisha Kent, 1820-1857.; Kephart, Horace, 1862-1931 ed. (New York : Outing publishing company, 1915)
"The following pages comprise chapters XX to XLVI of Dr. Kane's work 'The U.S. Grinnell expedition in search of Sir John Franklin: a personal narrative' (London and New York, 1854) omitting nothing but some scientific observations."--Introd. Illustrated lining-papers. Mode of access: Internet.